JIHAD DALAM PERSPEKTIF HADIS - Kamarudin, Kamarudin (State Institute of Islamic Studies (IAIN) Palu, 2008)
Jihâd is one of the Islamic main terms which is frequently misunderstood by the group of non Muslims. They tend to perceive jihâd as a holy war against the disbelievers. Based on this, to them, jihâd is identical to violence. The question is wither Islam truly a religion of violence?, or it is only a misunderstanding towards jihâd in Islam. It is true that the term jihâd possesses a significant position among the Muslims that many of them devote themselves to God by jihâd. Jihâd in Islam has passed over two periods, the period of Mecca and the period of Medina with differentf emphasis on jihad.Kata Kunci: jihad, perang suci, terorisme, kekerasan, perspektif hadis